Jet injection of dyed saline facilitates efficient peroral endoscopic myotomy - Khashab, Mouen A.; Messallam, Ahmed A.; Saxena, Payal; Kumbhari, Vivek; Ricourt, Ernesto; Aguila, Gerard; Roland, Bani Chander; Stein, Ellen; Nandwani, Monica; Inoue, Haruhiro; Clarke, John O. (Endoscopy, 2014)
Background and study aims: Peroral endoscopic myotomy (POEM) is technically challenging and time consuming. Repeated injection of dyed saline during tunneling is performed to enhance the demarcation between the submucosal layer and the muscularis propria. This process requires exchanging the knife for a catheter to spray dyed saline and is time consuming. This study aimed to describe a new method of injecting dyed saline through an integrated water jet channel during POEM. Patients and methods: POEM was performed using a triangular tip knife. Repeated jet injection of saline mixed with indigo carmine was performed whenever the submucosal dissection plane became unclear. Results: The study cohort consisted of nine patients (8 achalasia, 1 Jackhammer esophagus). All procedures were technically feasible and successful without any complications and resulted in the patients’ Eckhardt’s scores returning to normal. The mean submucosal tunnel length was 13.3 cm and the mean myotomy length was 9.9 cm. The mean procedure time was 127 minutes. Conclusion: The modified POEM technique with use of jet injection of dyed saline is simple and may render POEM easier and more efficient than the standard dissection method.